A New Virulent Isolate of Clover Yellow Vein Virus on Phaseolus vulgaris in Bulgaria. Issue 11 (15th March 2014) - Pasev, Gancho; Kostova, Dimitrina; Turina, Massimo
Abstract Potyviruses are a common threat for snap bean production in Bulgaria. During virus surveys of bean plots in the south central region, we identified an isolate of Clover yellow vein virus (ClYVV), designated ClYVV 11B, by indirect ELISA and RT‐PCR causing severe mosaic symptoms and systemic necrosis. Indirect and direct ELISA using ClYVV antisera differentiated the ClYVV isolate from Bean yellow mosaic virus (BYMV), but serological analysis could not distinguish the Bulgarian isolate ClYVV 11B from an Italian ClYVV isolate used as a reference (ClYVV 505/7). RT‐PCR analyses with specific primers revealed that both isolates were ClYVV. Sequence analysis of an 800 bp fragment corresponding to the coat protein coding region showed 94% identity at the nucleotide level between the two isolates. Phylogenetic analyses of aligned nucleotide sequences available in the database confirmed the existence of two groups of isolates, but ClYVV 11B and ClYVV505/7 belonged to the same group. We compared the virulence of both isolates on a set of differential cultivars and 19 bean breeding lines resistant to Bean common mosaic virus (BCMV) and Bean common mosaic necrosis virus (BCMNV): Bulgarian isolate ClYVV 11B was able to infect systemically all tested bean differential cultivars and breeding lines including those with genotypes Ibc3 and Ibc22; Italian isolate ClYVV 505/7 was not able to infect systemically some differentials with genotypes bc‐ubc1, bc‐ubc22, bc‐ubc2bc3, Ibc12, Ibc22, Ibc3. The role of bc3 gene as a source of resistance to potyviruses is discussed.